PENGARUH PROGRAM PINJAMAN MODAL TERHADAP NASABAH PERMODALAN NASIONAL MADANI MEKAAR SYARIAH DI DESA SUNGAI RUAN ULU KECAMATAN MARO SEBO ULU - Anzu Elvia Zahara; Jevi Saputra; Oni Novela (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research is motivated by the existence of a capital loan program provided by PNM Mekaar Syariah to underprivileged women who are ultra-micro entrepreneurs based on a fatwa and/or statement of sharia conformity from the National Sharia Council of the Indonesian Ulema Council. This research aims to determine whether or not there is an influence of the capital loan program on PNM Mekaar Syariah customers in Sungai Ruan Ulu Village, Maro Sebo Ulu District, Batanghari Regency. The number of samples in this study was 80 people and used a simple random sampling technique, namely a sampling method by selecting directly from the population and the opportunity for each member of the population to become a sample was very large. Simple regression analysis is used as a data analysis technique. The results of this research show that the capital loan program has an effect on PNM Mekaar Syariah customers in Sungai Ruan Ulu Village, Maro Sebo Ulu District, Batanghari Regency. Based on data analysis in this research, these variables are valid and reliable. When testing classical assumptions with a normal distribution, heteroscedasticity and multicollinearity do not occur